Multiculture, Community and Social Inclusion in New City Spaces - Kesten, Jamie (2012)
This thesis is interested in understanding the new migration patterns and changing geographies of multiculture taking place in the UK outside of the larger established cities and towns by investigating Milton Keynes (MK) as a new multicultural city space. Using a case study of MK's Ghanaian and Somali communities it explores how BME communities establish themselves as part of the wider local community and examines the ways in which local policy-makers and practitioners have responded to an increasingly multicultural and ethnically diverse population. The research focuses upon local sites of community construction such as schools, provision for young people and religious centres, reflecting, among other things, the particular formal and informal roles played by these sites. The thesis finds that people within MK are not living the 'parallel lives' crisis of the community cohesion discourse, but rather 'living apart' at times and also 'living together' at others, reinforcing the significance of place-based understandings in the context of new multicultural geographies. The research found that young people of Ghanaian and Somali origin often reflected positively on the sense of community present within MK's residential areas and demonstrated processes of negotiation and of both 'mixing' and 'non-mixing' within certain distinct social and geographic contexts. It also found that, in seeking to manage the emergent multicultural population, policy-makers and practitioners generally rely on identifying community organisations (and their leaders) with whom they can liaise. In doing so they may overlook the significant diversity of experiences which exist within the Ghanaian and Somali communities (and the extent to which these are subject to change) and are therefore less likely to deliver appropriate resources and interventions. The research findings indicated that how people themselves manage multiculture is much more fluid and able to be negotiated than cohesion discourses and formal policy makers imagine and assume